Fake news contra a vida: desinformação ameaça vacinação de combate à febre amarela - Teixeira, Adriana (2019)
The research entitled as Fake news against life: misinformation threats vaccination campaign as a control measure for yellow fever reads the operation of fake news that circulate content on Public Health through digital networks and messaging apps. Surveys conducted by the author of the dissertation show that in recent years, fake news – allied with anti-vaccination movements –, have contributed to reducing the immunization rates of the world population – a cause of deaths and of the return to eradicated diseases. In Brazil, the vaccination campaign to combat yellow fever was the first victim of fake news. However, before elaborating on the damages to life that this narrative entails by going viral on digital networks, this present research ponders on the origin of fake news – a word that arose in the nineteenth century to substitute the expression false news to signify the news fabricated and defrauded by the mass media and imposed as truth by magazines, newspapers, radios and TV networks. To get to this result, digital archives of English-language newspapers were consulted. This research also follows the course of fake news throughout two centuries – with the enumeration of the usages of important ecosystems of misinformation at different times in history - until we reach the communication in which the multiplicity of the senders of messages stand out. The digital environment grants new power to fake news that invade Public Health in a willingness to confront the voices of the State and Science. At this point in the dissertation, the corpus of the research rises: the posts with narratives against immunization that circulated through WhatsApp during the 2016 and 2018 yellow fever vaccination campaign. In order to understand the combination of arguments used by the misinformation and the convincing power of the fake in the dispute with other statements, the reading of these posts is made, essentially, through the theories formulated by the philosopher Michel Foucault on regimens of truth, discursive formation and enunciative function. That reflection opens the way to start understanding the fake news convincing mechanism in Public Health through the concept of biopolitics, also Foucault’s. Fake news work with the defense of life speech – so do the State, the Science and the pharmaceutical industry. Yet, when the purpose of immunization is put to the test and the behavior of the one who comes into contact with it is influenced, fake news mislead and subject life to danger. They kill